b) } \frac{\mathrm{d} h}{\mathrm{~d} x}=\frac{2 x}{\ln (2)\left(2 x^{2}+3\right)} \text { c) } \frac{\mathrm{d} h}{\mathrm{~d} x}=\frac{x}{2 \log _{2}\left(\sqrt{2 x^{2}+3}\right)} \text { d) } \frac{\mathrm{d} h}{\mathrm{~d} x}=\frac{2 x}{\log _{2}(2)\left(2 x^{2}+3\right)}-1 \text { (e) } \frac{\mathrm{d} h}{\mathrm{~d} x}=\frac{2 x}{\left(2 x^{2}+3\right)}-1 \text { f) } \frac{\mathrm{d} h}{\mathrm{~d} x}=\frac{2 x}{\ln (2)\left(2 x^{2}+3\right)}-1

Fig: 1

Fig: 2

Fig: 3

Fig: 4

Fig: 5

Fig: 6

Fig: 7

Fig: 8